2019
DOI: 10.2147/dmso.s193259
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neudesin in obesity and type 2 diabetes mellitus: the effect of acute fasting and weight reducing interventions</p>

Abstract: Context Neudesin has recently been identified as a novel regulator of energy expenditure in experimental animals; however, its role in humans remains unexplored. Objective The aim of this study was to assess the effects of obesity and type 2 diabetes mellitus (T2DM) along with selected weight reducing interventions on serum neudesin levels and adipose tissue mRNA expression. Patients and methods Fifteen obese subjects with T2DM undergoing end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
0
15
2
Order By: Relevance
“…However, the serum concentrations of neudesin detected by Karatas et al. (2021) are about thirty times higher than those reported in our paper and in most of the previously published papers ( 17 , 19 , 21 23 ). Celikkol et al.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, the serum concentrations of neudesin detected by Karatas et al. (2021) are about thirty times higher than those reported in our paper and in most of the previously published papers ( 17 , 19 , 21 23 ). Celikkol et al.…”
Section: Discussioncontrasting
confidence: 77%
“…Kratochvilova et al. (2019) found no differences in serum neudesin levels among obese adults (81% with T2MD) undergoing endoscopic bariatric procedures, patients with functional hypoglycemia and healthy controls ( 17 ). On the other hand, recently Karatas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Kratochvilova et al ( 20 ) also investigated serum neudesin levels and its mRNA expression in subcutaneous and visceral adipose tissue in obese subjects with or without type 2 diabetes. They found that serum neudesin concentrations in obese subjects, both with and without type 2 diabetes, did not differ from healthy lean control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Kratochvilova et al ( 20 ) also reported a possible role of neudesin in the development of obesity-related metabolic disturbances, based on the observed effects of acute fasting and selected weight-reducing interventions, like endoscopic duodenojejunal bypass liner implantation or gastric plication. An obese diabetic group undergoing duodenojejunal bypass liner implantation showed significantly increased concentrations of circulating neudesin.…”
Section: Discussionmentioning
confidence: 99%
“…Although neudesin was identified less than 20 years ago [ 164 ], it still remains mostly unexplored, and is only now becoming a subject of metabolism-related studies (in diseases, relating to obesity, diabetes mellitus, insulin resistance and PCOS) [ 34 , 167 , 168 , 169 , 170 , 171 , 172 ].…”
Section: Neudesinmentioning
confidence: 99%